Histopathological findings of the human great saphenous vein treated with endoluminal radio frequency ablation - Bedi, Harinder Singh; Calton, Nalini; Kwatra, Kanwardeep Singh; Tewarson, Vivek (International Surgery Journal, 2016)
Background: There is not much data on the histopathologic effect of Radio Frequency Ablation (RFA) on the human vein. In order to better understand the exact mechanism and sites of action of the device we studied in detail the histological changes in the vessel wall of the Great Saphenous Vein (GSV) after it was subjected to RFA. Methods: We studied the effect of RFA on 5 pieces of the human GSV from 5 different patients. The harvested vein was subjected to radiofrequency ablation and then studied in detail by histopathology. Results: On gross inspection immediately during the radiofrequency application, the vein shrunk lengthwise and in diameter with marked narrowing of the lumen and charring. On histopathology the vein showed a photo-disruption in the form of total loss of endothelium. There was a sub-endothelial hematoma with small haemorrhages in the muscle coat and thermal coagulation of smooth muscle. The thermal effect was pan-mural and extending up to the adventitia. Conclusion: Our findings have implications for a better understanding of the mechanism of the action of radiofrequency on the venous system and for further improvements in technique and hardware to improve efficacy and reduce the side effects during endovenous therapy for varicose veins.